An educational programme based on salutogenesis theory on childbirth fear and delivery method among nulliparous women: A mixed methods research protocol - Safieh Kananikandeh; Farkhondeh Amin Shokravi; Mojgan Mirghafourvand; Shayesteh Jahanfar (Wiley, 2023)
Abstract Aim Designing, executing and testing a training intervention based on enhanced concepts of salutogenesis theory for managing fear of childbirth and choice of delivery method among nulliparous women. Design A Sequential‐Exploratory Mixed Methods Research. Methods In the first phase (qualitative approach), the determinants of childbirth fear among nulliparous women will be explored. In the second phase (systematic review), the factors of childbirth fear among them will be summarized. In the third phase, the content of the educational intervention is developed based on the common factors of childbirth fear obtained from the previous two phases of the study. In the fourth phase (randomized controlled trial), two intervention and the control groups will be compared based on primary and secondary outcomes. Discussion Using salutogenesis theory in a few interventional studies on various health areas has produced promising results. Based on the evidence, women had less sense of coherence with a strong childbirth fear. Therefore, developing an effective intervention based on this theory can probably help manage childbirth fear and reduce the costs of any potential consequences.